Introduction - Lal, B. (Springer Nature, 2022)
This chapter introduces the main aspects of this book by providing relevant and summarized background on the mitigation of hydrate formation in drilling mud for both deepwater drilling and hydrate sediment drilling. The need for novel and effective drilling mud systems for hydrate sediment drilling operations is highlighted. The details of hydrate drilling mud systems are presented and discussed in this chapter to provide a clear overview and research progress on hydrae drilling mud systems. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.